NOD Mice Having a Lyn Tyrosine Kinase Mutation Exhibit Abnormal Neutrophil Chemotaxis. Issue 7 (27th March 2017) - Wu, Yue; Hannigan, Michael; Zhan, Lijun; Madri, Joseph A.; Huang, Chi‐Kuang
Abstract : Neutrophils from NOD (Non‐Obese Diabetic) mice exhibited reduced migration speed, decreased frequency of directional changes, and loss of directionality during chemotaxis (compared to wild‐type [WT] C57BL/6 mice). Additionally, F‐actin of chemotaxing NOD neutrophils failed to orient toward the chemoattractant gradient and NOD neutrophil adhesion was impaired. A point mutation near the autophosphorylation site of Lyn in NOD mice was identified. Point mutations of G to A (G1412 in LynA and G1199 in LynB) cause a change of amino acid E393 (glutamic acid) to K (lysine) in LynA (E393 →K) (E372 of LynB), affecting fMLP‐induced tyrosine phosphorylation. These data indicate that the Lyn mutation in NOD neutrophils is likely responsible for dysregulation of neutrophil adhesion and directed migration, implying the role of Lyn in modulating diabetic patient's susceptibility to bacterial and fungal infections. J. Cell. Physiol. 232: 1689–1695, 2017. © 2016 Wiley Periodicals, Inc. Abstract : A specific Lyn kinase mutation has been documented in NOD mice which affects neutrophil directed migration. This may thus affect response to infections in this murine model of diabetes.